Menakar Literasi Keuangan dan Pendapatan Terhadap Perilaku Manajemen Keuangan Bagi Dokter Gigi Dengan Gaya Hidup Sebagai Mediasi - Ni Made Vivi Cintya Dewi; Gede Sri Darma (Universitas Pendidikan Nasional, 2021)
The purpose of this study was to determine the effect of financial literacy and income partially on financial management behavior and dentist's lifestyle and to determine the influence of lifestyle in mediating financial literacy and income partially on financial management behavior for dentists. The population of this study were all dental practices in Denpasar City. According to the Association of Indonesian Dentists (PDGI), the number of dental practices in Denpasar City is 607 units which can be accessed at www.certification.pdgi.or.id. The number of samples was calculated using the Slovin formula so that the respondents obtained were 86 dentists in Denpasar City. The analytical tool used in this research is Partial Least Square/PLS (Component-based SEM) analysis. The results of the analysis of this study indicate that the higher the financial literacy and income, the higher the behavior of the dentist's financial management then the higher the financial literacy and income, the higher the dentist's lifestyle. The results also show that the higher the lifestyle, the higher the dentist's financial management behavior. Furthermore, the higher the lifestyle (full mediated) affects financial literacy, the higher the financial management behavior. As well as lifestyle affects (partial mediated) income, the higher the financial management behavior.